Morphoanatomic characterization of the stem and the leaf of Tabernaemontana catharinensis A.DC (Apocynaceae) and antimutagenic activity of its leaves - D.G.G. GUIDOTI; D.T. GUIDOTI; C.L.M.S.C. ROCHA; K.S.M. MOURÃO (Universidade Estadual Paulista, 2015)
ABSTRACT Tabernaemontana catharinensis A. DC (Apocynaceae) is used as a medicinal plant by the population. In order to contribute to the safe use of the plant as herbal medicine, this study aimed to morphoanatomically characterize the aereal vegetative organs of T. catharinensis and to evaluate the leaves' mutagenic and antimutagenic activities. Histological blades of leaves and stem of T. catharinensis were performed; the methionine system (methG1) and Aspergillusnidulans conidia germination analysis were employed for mutagenic and antimutagenic evaluation. The morphoanatomic analysis did not show trichomes in the stem, petiole and leaf. Besides, it was observed both the presence of bi-collateral bundles - except in the foliar apex where the bundles were from the collateral type - as well as anamphistomatic leaf with paracyte stomata and sub-epidermal layer in the region of the leaf edges. The mutagenicity/antimutagenicity trial indicated a significant decrease of mutation frequency in comparison with the control group and showed that the T. catharinensis had antimutagenic activity within the type, time and form of treatment. Since the germination test showed that the conidia germination was accelerated from the bud phase, activities at the cell cycle level and polarized growth proved to be possible. The morphoanatomic analysis of the leaf and stem associated with the mutagenic and antimutagenic analyses contributes to the safe use of the plant by humans and also for the quality control of a possible phytotherapeutic drug.